The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0215016
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in spatial accessibility of U.S. healthcare providers

Abstract: Background Growing physician maldistribution and population demographic shifts have contributed to large geographic variation in healthcare access and the emergence of advanced practice providers as contributors to the healthcare workforce. Current estimates of geographic accessibility of physicians and advanced practice providers rely on outdated “provider per capita” estimates that have shortcomings. Purpose To apply state of the art methods to estimate spatial access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 27 publications
3
49
1
Order By: Relevance
“…Establishing and maintaining trust with communities through grassroots organizing, participation and collaboration is foundational to that goal. Additionally, assessing Hauer, 2017;Hinojosa & Meléndez, 2018;Hunter, 2005;IOM, 2020;Kim, 2020;Martin, 2018;Malo, 2019;McMichael et al, 2012;Robinson et al, 2020;Rudowitz et al, 2006;Siders, 2019;The Nansen Initiative, 2015;Universiteit Maastricht et al, 2016;Watts et al, 2015Health Systems Abramitzky et al 2013Baumgartner et al, 2020;Department for Professional Employees, 2016;Garrett and Gangopadhyaya 2020;Hersher and Benincasa 2019;Naylor et al, 2019;Nekoie-Moghadam et al, 2016; Office of the Assistant Secretary for Preparedness and Response, 2016; Paybarah et al 2020; Reeves 2020; Rice et al, 2013;Roser-Renouf et al, 2016;Rudowitz et al, 2006;Tikkanen et al, 2020 Climate Migration andHealth Systems Perch-Nielsen et al, 2008;McMichael et al, 2012;Roser-Renouf et al, 2016;Schwerdtle et al, 2018;Sendai Framework for Disaster Risk Reduction, 2015-2030Watts et al, 2015 Note: This table delineates the resources reviewed for climate migration, health systems, and the intersection of the two fields. There are some overlaps for resources that grappled with multiple elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing and maintaining trust with communities through grassroots organizing, participation and collaboration is foundational to that goal. Additionally, assessing Hauer, 2017;Hinojosa & Meléndez, 2018;Hunter, 2005;IOM, 2020;Kim, 2020;Martin, 2018;Malo, 2019;McMichael et al, 2012;Robinson et al, 2020;Rudowitz et al, 2006;Siders, 2019;The Nansen Initiative, 2015;Universiteit Maastricht et al, 2016;Watts et al, 2015Health Systems Abramitzky et al 2013Baumgartner et al, 2020;Department for Professional Employees, 2016;Garrett and Gangopadhyaya 2020;Hersher and Benincasa 2019;Naylor et al, 2019;Nekoie-Moghadam et al, 2016; Office of the Assistant Secretary for Preparedness and Response, 2016; Paybarah et al 2020; Reeves 2020; Rice et al, 2013;Roser-Renouf et al, 2016;Rudowitz et al, 2006;Tikkanen et al, 2020 Climate Migration andHealth Systems Perch-Nielsen et al, 2008;McMichael et al, 2012;Roser-Renouf et al, 2016;Schwerdtle et al, 2018;Sendai Framework for Disaster Risk Reduction, 2015-2030Watts et al, 2015 Note: This table delineates the resources reviewed for climate migration, health systems, and the intersection of the two fields. There are some overlaps for resources that grappled with multiple elements.…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing physician geographic maldistribution, which further contributes to the unequal distribution of health resources across the country. Additionally, there is a shortage of primary care physicians (Hinojosa & Meléndez, 2018) with little financial incentive to pursue that career (Naylor et al, 2019). Physicians are more likely to move to urban centres in the mid-Atlantic and northeast.…”
Section: Gaps In the American Health Systemmentioning
confidence: 99%
“…Therefore, it is questionable if current concepts of hospital planning allow an adequate allocation of hospital resources [14]. Floating Catchment Area (FCA) methods (as a special case of a gravity model) could improve this allocation process since they integrate both the concept of the need for health care (as suggested by the realistic theory) and a sophisticated measure of spatial accessibility [17][18][19]. Delamater et al further showed that FCA methods can provide predictions of patient utilization patterns [20].…”
mentioning
confidence: 99%
“…This study also only use xed catchment size of 30 minutes, regardless of type of clinic although bigger clinic should theoretically have bigger catchment size or service coverage [54,72]. Therefore the use of multiple catchment sizes depending on type of clinic or different types of rural areas also could further improve the precision of the E2SFCA measure, especially for a national-level or a larger scale study [32,73]. This study also demonstrates the practicability of data integration, bene ting from multiple databases that routinely collected by the government agencies.…”
Section: Discussionmentioning
confidence: 99%